Asosiasi antara Tingkat Pengetahuan dan Sikap Terhadap Perilaku Siswi dalam Pencegahan Infeksi Menular Seksual - Margiyati; Kurniawati, Erna Yovi (Agribiohealth (Journal of Agriculture, Biology & Health Sciences), 2025)
Sexually transmitted infections (STIs) remain a major reproductive health concern among adolescents, particularly female students with varying levels of knowledge and attitudes toward preventive behavior. This study aimed to analyze the relationship between knowledge and attitude toward preventive behavior against STIs. This research employed a descriptive-correlational design with a cross-sectional approach, conducted at Abu Bakar Integrated Islamic Senior High School, Yogyakarta. The population consisted of 29 female students selected through total sampling. Data were collected using validated and reliable standardized questionnaires and analyzed using multiple linear regression with a 0.05 significance level. The analysis revealed no significant relationship between knowledge and attitude with STI preventive behavior (p>0.05). The R² value of 0.170 indicated that knowledge and attitude contributed only 17% to preventive behavior, while 83% was influenced by other factors. Knowledge and attitude were not the dominant factors shaping preventive behavior toward STIs. Future educational interventions should integrate social, cultural, and religious determinants to enhance adolescent health behavior.